Ceramic Electronic Components

The ceramic electronic component addresses plating defects by incorporating a glass frit and high melting point oxide in the baked electrode layer, ensuring both effective plating and strong bonding, thereby improving reliability under thermal stress.

JP7606369B2Active Publication Date: 2024-12-25TDK CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021036614
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-08
Publication Date
2024-12-25
Estimated Expiration
2041-03-08

AI Technical Summary

Technical Problem

Conventional ceramic electronic components face challenges in achieving both good plating properties and high bonding strength of external electrodes due to the risk of plating defects caused by glass frit exposure, which can lead to poor adhesion and peeling of the baked electrode from the element body.

Method used

The ceramic electronic component includes a baked electrode layer with a first region containing glass frit and a second region with a high melting point oxide, optimizing the composition and distribution of these components to enhance bonding strength and plating properties.

Benefits of technology

The proposed configuration improves plating properties and bonding reliability of the external electrode, preventing peeling even under thermal stress, by suppressing glass frit precipitation and enhancing mutual diffusion between the electrode and the element body.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007606369000007
    Figure 0007606369000007
  • Figure 0007606369000008
    Figure 0007606369000008
  • Figure 0007606369000009
    Figure 0007606369000009
Patent Text Reader

Abstract

To provide a ceramic electronic component having a bake electrode with an excellent plating property and a high joint reliability for an element body.SOLUTION: The ceramic electronic component includes: an element body including a ceramic layer mainly including a perovskite compound expressed by ABO3 and an internal electrode layer; and an external electrode formed in an end surface of the element body, the external electrode being electrically connected to at least a part of the internal electrode layer. The external electrode has a bake electrode layer. The bake electrode layer includes a first region in contact with an end surface of the element body, the first region being located near the joint interface with the element body, and a second region located outside the first region, the second region forming the outer surface of the bake electrode layer. The first region contains glass frit containing B, Zn, and Si and the second region contains an oxide with a higher melting point than Cu.SELECTED DRAWING: Figure 2B
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a ceramic electronic component having external electrodes. [Background technology]

[0002] As shown in Patent Document 1, a ceramic electronic component is known that includes an element body containing ceramic components and external electrodes formed on the outer surface of the element body. Baked electrodes are widely used as the external electrodes of ceramic electronic components, and can be formed by applying a conductive paste containing conductor powder and glass frit to the surface of the element body and baking it. In Patent Document 1, the solder wettability of the external electrodes is improved by forming plated electrodes on the baked electrodes as described above.

[0003] However, the external electrodes disclosed in Patent Document 1 may cause plating defects. Specifically, the baked electrodes contain glass frit, which may be exposed on the outer surface of the baked electrodes, causing plating defects such as poor adhesion of the plated electrodes and non-precipitation. In order to suppress such plating defects, it is conceivable to reduce the content of glass frit in the baked electrodes. However, reducing the content of glass frit reduces the bonding strength of the baked electrodes to the surface of the element body, and there is a risk that the baked electrodes will peel off from the surface of the element body.

[0004] As described above, in the conventional technology as shown in Patent Document 1, it was difficult to achieve both the plating property of the baked electrode (ease of forming the plated electrode) and the bonding strength to the element body. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Publication No. 4-171912 Summary of the Invention [Problem to be solved by the invention]

[0006] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a ceramic electronic component having baked electrodes which have good plating properties and high bonding reliability to the element body. [Means for solving the problem]

[0007] In order to achieve the above object, a ceramic electronic component according to the present invention comprises: an element body including a ceramic layer and an internal electrode layer; and an external electrode formed on an end surface of the element body and electrically connected to at least one end of the internal electrode layer; The ceramic layer is made of ABO 3 The perovskite-type compound represented by the formula the external electrodes have baked electrode layers, the fired electrode layer has a first region that is in contact with the end face of the element body and is located near a joint boundary with the element body, and a second region that is located outside the first region and constitutes an outer surface of the fired electrode layer, The first region includes a glass frit containing at least B, Zn, and Si, and the second region includes an oxide having a melting point higher than that of Cu.

[0008] The inventors have found that by providing a ceramic electronic component with the above-mentioned configuration, the plating properties of the baked electrodes are improved, and the bonding reliability of the external electrodes (baked electrodes) to the element body is improved. The reason why the above effects are obtained is not necessarily clear, but the following reasons are thought to be the cause.

[0009] First, as described above, in the ceramic electronic component of the present invention, the second region containing a high melting point oxide is present on the outer surface of the fired electrode layer that will come into contact with the plated electrode. It is believed that the presence of a certain high melting point oxide on the outer surface in this manner can suppress the precipitation of nonmetallic components such as glass frit on the outer surface of the fired electrode layer. As a result, plating defects can be suppressed when forming a plated electrode on the fired electrode.

[0010] In addition, in the ceramic electronic component of the present invention, a glass frit containing a predetermined element is contained in the first region that is bonded to the end face of the element body. The glass frit is believed to wet and spread throughout the conductor and between the conductor and the element end face, improving the bonding strength of the baked electrode layer to the element body. As a result, in the ceramic electronic component of the present invention, peeling of the external electrode from the end face of the element body can be suppressed even if the component is subjected to thermal shock.

[0011] In particular, when the glass frit in the first region and the oxide in the second region satisfy a predetermined composition ratio, the plating properties and bonding reliability of the external electrodes (fired electrode layers) are further improved.

[0012] That is, in the glass frit contained in the first region, If the sum of the B content, Zn content, and Si content is 1 molar part, Preferably, the Zn content is 0.20 to 0.35 parts by mol, the Si content is 0.10 to 0.30 parts by mol, and B is the remainder.

[0013] Also, preferably, the oxide contained in the second region contains Zn and Si as main components, and the molar ratio of the Zn content to the Si content in the oxide (Zn / Si) is 1.5 to 2.4.

[0014] Alternatively, preferably, the oxide contained in the second region is Zn 2 SiO 4 It is.

[0015] Preferably, a boundary layer is present at the end of the ceramic layer in contact with the external electrode at the end face of the element body, and the boundary layer preferably contains Zn, Si, and an A-site element of the perovskite compound.

[0016] The presence of a boundary layer containing a specific element at the end of the ceramic layer as described above further improves the bonding reliability of the fired electrode to the element body. The reason for this further improvement in bonding reliability is not necessarily clear, but is thought to be related to the interdiffusion phenomenon. Specifically, it is thought that the bonding strength of the external electrode is further improved by the mutual diffusion of common elements (Zn, Si, A-site elements) of the external electrode (particularly the glass frit) and the element body (particularly the boundary layer and ceramic layer) and elements that are easily dissolved in both.

[0017] In addition, the boundary layer satisfies a predetermined composition, thereby further improving the bonding reliability of the external electrode. That is, in the boundary layer, when the sum of the content of Zn, the content of Si, and the content of the A-site element is taken as 1 molar part, the content of the A-site element is preferably 0.3 molar parts to 0.45 molar parts, the content of Zn is 0.15 molar parts to 0.45 molar parts, and the remainder is Si. Alternatively, the main component of the boundary layer is (Ca, Sr) 2 Zn(Si 2 O 7 ) is preferred.

[0018] Preferably, in a cross section of the fired electrode layer, the area ratio of the conductor in the first region is 30% to 60%.When the fired electrode layer satisfies the above requirements, the bonding reliability of the external electrodes is further improved.

[0019] Preferably, in a cross section of the fired electrode layer, the area ratio of the conductor in the second region is 70% to 90%.When the fired electrode layer satisfies the above requirements, the plating properties of the external electrodes are further improved. [Brief description of the drawings]

[0020] [Figure 1A] FIG. 1A is a cross-sectional view showing a multilayer ceramic capacitor according to one embodiment of the present invention. [Figure 1B] FIG. 1B is a cross-sectional view showing a multilayer ceramic capacitor according to another embodiment of the present invention. [Figure 2A]FIG. 2A is an enlarged cross-sectional view of a main portion of a region IIA shown in FIG. 1A. [Figure 2B] FIG. 2B is an enlarged cross-sectional view of a main portion of region IIB shown in FIG. 1B. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] Hereinafter, the present invention will be described in detail based on the embodiments shown in the drawings.

[0022] First embodiment 1A will be described as an example of a ceramic electronic component according to the present invention. The multilayer ceramic capacitor 2 has an element body 4 and a pair of external electrodes 6 formed on the outer surface of the element body 4.

[0023] 1A is generally shaped like a rectangular parallelepiped, with two end faces 4a facing each other in the X-axis direction, two side faces 4b facing each other in the Y-axis direction, and two side faces 4b facing each other in the Z-axis direction. However, the shape of the element body 4 is not particularly limited, and may be an elliptical cylinder, a circular cylinder, or another prismatic shape. The outer dimensions of the element body 4 are also not particularly limited, and may be, for example, a length L0 in the X-axis direction of 0.4 mm to 5.7 mm, a width W0 in the Y-axis direction of 0.2 mm to 5.0 mm, and a height T0 in the Z-axis direction of 0.2 mm to 3.0 mm.

[0024] In this embodiment, the X-axis, Y-axis, and Z-axis are perpendicular to each other. In this embodiment, the term "inner side" refers to a side closer to the center of the multilayer ceramic capacitor 2, and the term "outer side" refers to a side farther from the center of the multilayer ceramic capacitor 2.

[0025] The element body 4 has ceramic layers 10 and internal electrode layers 12 that are substantially parallel to a plane including the X-axis and Y-axis, and inside the element body 4, the ceramic layers 10 and the internal electrode layers 12 are alternately stacked along the Z-axis direction. Here, "substantially parallel" means that most parts are parallel, but there may be some parts that are not parallel, and the ceramic layers 10 and the internal electrode layers 12 may be somewhat uneven or inclined.

[0026] The ceramic layer 10 is mainly composed of a compound represented by the general formula ABO 3 Here, the main component of the ceramic layer 10 refers to a component that is contained in an amount of 80 mol % or more with respect to the entire ceramic layer 10. In this embodiment, the perovskite compound preferably contains at least Ca and Sr in the A site, and among perovskite compounds, it is more preferable that the main component of the ceramic layer 10 is calcium strontium zirconate (CSZ).

[0027] Calcium strontium zirconate is generally known by the formula (Ca 1-x Sr x )m(Zr 1-y-z Ti y Hf z )O 3 In the above composition formula, the symbols x, y, z, and m each represent an element ratio, and the element ratio is not particularly limited and can be set within a known range.

[0028] For example, m indicates the element ratio of the A site to the B site, and can generally be in the range of 0.9 to 1.1. Also, x indicates the element ratio of Sr in the A site, and can be 0≦x≦1. That is, the ratio of Ca to Sr is arbitrary, and only one of them may be contained. Also, a small amount of Ba may be contained in the A site. y indicates the element ratio of Ti in the B site, and z indicates the element ratio of Hf in the B site. In this embodiment, it is preferable that 0≦y+z≦0.1. The element ratio of oxygen (O) in the above composition formula may be slightly deviated from the stoichiometric composition.

[0029] In addition to the above-mentioned main components, the ceramic layer 10 may contain auxiliary components. Examples of the auxiliary components include Mn compounds, Si compounds, Al compounds, Mg compounds, Li compounds, and B compounds, and the types, combinations, and amounts of the auxiliary components added are not particularly limited.

[0030] The average thickness Td (interlayer thickness) per layer of the ceramic layers 10 is not particularly limited, and can be, for example, 100 μm or less, and preferably 30 μm or less. The number of layers of the ceramic layers 10 may be determined according to the desired characteristics, and is not particularly limited. For example, it can be 20 layers or more, and more preferably 50 layers or more.

[0031] On the other hand, the internal electrode layers 12 are laminated between the ceramic layers 10, and the number of layers is determined according to the number of layers of the ceramic layers 10. The average thickness Te of each of the internal electrode layers 12 is not particularly limited, and is preferably, for example, 3.0 μm or less.

[0032] Furthermore, the multiple internal electrode layers 12 are stacked such that one end is alternately exposed on two end faces 4a facing each other in the X-axis direction of the element body 4. A pair of external electrodes 6 are formed on one end face 4a of the element body 4, and are electrically connected to the exposed ends of the alternately arranged internal electrode layers 12. By forming the internal electrode layers 12 and the external electrodes 6 in this manner, the external electrodes 6 and the internal electrode layers 12 form a capacitor circuit.

[0033] That is, the internal electrode layer 12 serves to apply a voltage to each ceramic layer 10 as a part of the capacitor circuit. Therefore, the material of the internal electrode layer 12 includes a conductive material. Specific examples of the material include Cu, Ni, Ag, Pd, Au, Pt, or an alloy containing at least one of these metal elements. More preferably, the conductive material included in the internal electrode layer 12 is Ni or a Ni-based alloy, since the material of the ceramic layer 10 has reduction resistance. In addition, when Ni or a Ni-based alloy is the main component, one or more types of subcomponents for the internal electrode selected from Mn, Cu, Cr, etc. may be included.

[0034] In addition to the conductive material, the internal electrode layer 12 may contain the ceramic components contained in the ceramic layer 10 as co-materials, and may contain trace amounts (for example, about 0.1 mass % or less) of non-metallic components such as S and P.

[0035] 1A, the external electrode 6 of this embodiment integrally has an end surface portion formed on the end surface 4a in the X-axis direction of the element body 4, and extended portions formed at the ends in the X-axis direction on the four side surfaces 4b of the element body 4. That is, the pair of external electrodes 6 are each formed so as to wrap around from the end surface 4a to the side surfaces 4b of the element body 4. The pair of external electrodes 6 are insulated so as not to contact each other in the X-axis direction.

[0036] As described above, in this embodiment, the extensions of the external electrodes 6 are formed on each of the four side surfaces 4b of the element body 4. However, the extensions of the external electrodes 6 are not essential, and the external electrodes 6 may be composed of only the end surface portions. Alternatively, when the multilayer ceramic capacitor 2 is surface-mounted on a substrate, it is sufficient that the extensions of the external electrodes 6 are formed on at least the side surface 4b facing the mounting surface of the substrate, and they do not have to be formed on the side surface 4b opposite the mounting surface.

[0037] Fig. 2A is a schematic cross-sectional view in which a joint boundary 46 between the external electrode 6 and the element body 4 is enlarged. Note that Fig. 2A shows one of a pair of external electrodes 6, but the other external electrode 6 has the same characteristics as those shown in Fig. 2A. Hereinafter, detailed characteristics of the external electrode 6 in this embodiment and the joint state between the external electrode 6 and the element body 4 will be described with reference to Fig. 2A.

[0038] As shown in Fig. 2A, the external electrode 6 has a baked electrode layer 6a containing a conductor 61 and a non-metallic component 62, and the baked electrode layer 6a is in contact with the outer surface (end surface 4a) of the element body 4. The external electrode 6 may be composed of a single electrode layer, or may be composed of a plurality of electrode layers stacked together. Preferably, as shown in Fig. 2A, the external electrode 6 has a plated electrode layer 6b. By forming the plated electrode layer 6b, the solder wettability of the external electrode 6 is improved.

[0039] When the external electrode 6 is composed of a plurality of electrode layers, the baked electrode layer 6a is formed so as to be in contact with the outer surface of the element body 4, and another baked electrode layer, a resin electrode layer, or a plated electrode layer is formed on the baked electrode layer 6a. Fig. 2A shows an example of an external electrode 6 having a three-layer structure of a baked electrode layer 6a-Ni plated layer 6b1-Sn plated layer 6b2 (laminate in the order shown).

[0040] The average thickness Ts of the fired electrode layer 6a in contact with the end face 4a may be 5 μm to 200 μm, and preferably 10 μm to 50 μm. When the external electrode 6 is composed of multiple layers, the average thickness Tt of the external electrode 6 may be about 5 μm to 300 μm, and preferably 100 μm or less.

[0041] In this embodiment, the fired electrode layer 6a is divided into at least two regions, a first region 6a1 and a second region 6a2.

[0042] The first region 6a1 is in contact with the end face 4a of the element body 4, and is located near the joint boundary 46 with the element body 4. More specifically, the first region 6a1 is within a predetermined distance t1 from the joint boundary 46 toward the outside in the X-axis direction, and the predetermined distance t1 is preferably 1 / 4 to 3 / 4 times the average thickness Ts of the fired electrode layer 6a (i.e., 1 / 4≦t1 / Ts≦3 / 4).

[0043] On the other hand, the second region 6a2 is located outside the first region 6a2 and constitutes the outer surface 6ab of the baked electrode layer 6a. More specifically, the second region 6a2 is within a range of a predetermined distance t2 from the outer surface 6ab toward the inside in the X-axis direction, and the predetermined distance t2 is preferably 1 / 4 to 3 / 4 times the average thickness Ts of the baked electrode layer 6a (i.e., 1 / 4≦t2 / Ts≦3 / 4). In other words, the second region 6a2 is a region near the outer surface that contacts the plated electrode layer 6b.

[0044] The first region 6a1 and the second region 6a2 are distinguished from each other by the following procedure: In the cross section of the fired electrode layer 6a as shown in Fig. 2A, a provisional line is drawn substantially parallel to the X-axis (substantially perpendicular to the end face 4a), and the area within a predetermined distance t1 along the provisional line is defined as the first region 6a1, and the area within a predetermined distance t2 along the provisional line is defined as the second region 6a2.

[0045] The first region 6a1 and the second region 6a2 are both part of the fired electrode layer 6a and contain a conductor 61 and non-metallic components 62 dispersed in the conductor 61, but the first region 6a1 and the second region 6a2 differ in the composition of the non-metallic components 62 and the content ratio of the conductor 61. The characteristics of the first region 6a1 and the second region 6a2 are described in detail below.

[0046] In the first region 6a1, glass frit 621 is included as the nonmetallic component 62, and the glass frit 621 is dispersed in the conductor 61. Note that the nonmetallic component 62 in the first region 6a1 may include voids, oxide particles, and the like (not shown) in addition to the glass frit 621.

[0047] The glass frit 621 is amorphous glass containing at least B, Zn, and Si, and the softening temperature of the glass frit 621 is lower than the melting point of the conductor 61. The inclusion of the glass frit 621 in the first region 6a1 in contact with the bond boundary 46 improves the sinterability and bond strength of the baked electrode layer 6a. It is believed that when the baked electrode layer 6a is formed, the glass frit 621 softens and penetrates into gaps inside the baked electrode layer 6a and into parts of the bond boundary 46, thereby enhancing the bond of the metal powder (raw material powder of the conductor 61) and the bond of the baked electrode layer 6a to the element body 4.

[0048] Moreover, the glass frit 621 preferably satisfies the following composition ratio. That is, assuming that the sum of the content of B, the content of Zn, and the content of Si is 1 part by mol, the content of Zn is preferably 0.20 parts by mol to 0.35 parts by mol, the content of Si is preferably 0.10 parts by mol to 0.30 parts by mol, and the remainder is B (preferably the content of B is 0.40 parts by mol to 0.70 parts by mol). When the glass frit 621 satisfies the above composition ratio, the bonding strength of the fired electrode layer 6a to the element body 4 is further improved.

[0049] The above-mentioned three elements (B, Zn, and Si) are the main elements of the glass frit 621, and the total content of the three elements excluding oxygen in the glass frit 621 is preferably 50 mol % or more, and more preferably 70 mol % to 80 mol %. In addition to the above-mentioned main elements, the glass frit 621 preferably contains A-site elements constituting the perovskite compound of the ceramic layer 10, and more preferably Ca and / or Sr. When the glass frit 621 contains A-site elements such as Ca and Sr, the bonding strength of the fired electrode layer 6a tends to be further improved.

[0050] The content of A-site elements such as Ca and Sr in the glass frit 621 is preferably 0.01 to 0.2 molar parts, and more preferably 0.05 to 0.2 molar parts, relative to 1.0 molar part of the total content of the main elements. Furthermore, the glass frit 621 may contain Al, Y, Zr, Mn, Mg, Ti, K, Na, Ba, etc.

[0051] On the other hand, the second region 6a2 contains a high melting point oxide 622 having a melting point higher than Cu as the nonmetallic component 62, and may also contain voids, oxide particles, etc. (not shown). Here, in this embodiment, the "melting point" refers to the temperature at which an oxide begins to melt, and indicates the solidus temperature in a phase diagram.

[0052] In this embodiment, the melting point of the conductor 61 is higher than the softening temperature of the glass frit 621, and the melting point of the high-melting-point oxide 622 is higher than the melting point of the conductor 61. The high-melting-point oxide 622 is contained in the second region 6a2 in contact with the plated electrode layer 6b, thereby suppressing non-precipitation and adhesion defects of the plated electrode layer 6b. This is believed to be because the high-melting-point oxide 622 suppresses the precipitation of glass components on the outer surface 6ab.

[0053] The high melting point oxide 622 preferably contains Zn and Si as main components, and more preferably satisfies the following composition ratio. That is, in the high melting point oxide 622, the molar ratio of the Zn content to the Si content (Zn / Si) is more preferably 1.5 to 2.4. More specifically, the high melting point oxide 622 is preferably Zn 2 SiO 4 It is preferable that:

[0054] The high melting point oxide 622 satisfying the above composition is easily bonded to the glass frit 621, and contributes to improving the sinterability and bonding strength of the baked electrode layer 6a. In addition, it is considered that the high melting point oxide 622 satisfying the above composition is unlikely to cause compositional fluctuations even when bonded to the glass frit 621. In other words, when the high melting point oxide 622 has a predetermined composition, it is considered that the high melting point oxide 622 can be prevented from chemically reacting with the glass frit 621 to be vitrified or to have a low melting point. As a result, the precipitation of glass components on the outer surface 6ab of the baked electrode layer 6a can be more effectively prevented, and the plating property of the baked electrode layer 6a is further improved.

[0055] The high melting point oxide 622 may be present not only in the second region 6a2 but also in the first region 6a1. Similarly, the glass frit 621 may be present inside the second region 6a2. In particular, the glass frit 621 and the high melting point oxide 622 may be present in a mixed state between the first region 6a1 and the second region 6a2.

[0056] However, it is preferable that the glass frit 621 is not substantially exposed to the outer surface 6ab. In other words, it is preferable that the glass frit 621 is not substantially in contact with the plated electrode layer 6b. More specifically, in the cross section of the baked electrode layer 6a as shown in FIG. 2A, it is preferable that the number of contact points of the glass frit 621 with the plated electrode layer 6b is 3 or less per 100 μm.

[0057] The number of contact points can be measured by counting the number of contact points contained within a length of 100 μm of the outer surface 6ab in cross-sectional observation photographed by SEM or the like. The length of the outer surface 6ab means the length of the boundary line between the baked electrode layer 6a and the plated electrode layer 6b, and the boundary line may be meandering or partially unclear. When measuring the number of contact points, it is not necessary to accurately measure the meandering or unclear parts of the boundary line. The cross-sectional photograph is taken so that one side of the boundary line (outer surface 6ab) is substantially parallel to the boundary line, and the width of the cross-sectional photograph can be regarded as the length of the boundary line (the length of the outer surface 6ab).

[0058] The conductor 61 in the first region 6a1 and the conductor 61 in the second region 6a2 may have different compositions, but preferably have the same composition. The conductor 61 in the fired electrode layer 6a is Cu or a Cu alloy. When the conductor 61 is a Cu alloy, the conductor 61 may contain elements other than Cu, such as Al, Ni, Ag, Pd, Sn, Zn, P, Fe, and Mn. The amount of elements other than Cu is preferably 5 molar parts or less per 100 molar parts of Cu.

[0059] In the first region 6a1, the average area ratio A1 of the conductor 61 in the cross section of the first region 6a1 is preferably 30% to 60%. On the other hand, in the second region 6a2, the average area ratio A2 of the conductor 61 in the cross section of the second region 6a2 is preferably 70% to 90%. As described above, the optimal content ratio of the conductor 61 is different between the first region 6a1 and the second region 6a2, and it is preferable that A2 of the second region 6a2 is larger than A1 of the first region 6a1, and it is more preferable that A2 / A1 is 1.3 to 2.4. When the average area ratios A1 and A2 satisfy the above requirements, the plating property and bonding reliability of the fired electrode layer 6a can be more suitably achieved.

[0060] The external electrode 6 can be analyzed by cross-sectional observation using a SEM (scanning electron microscope) or a STEM (scanning transmission electron microscope). For example, the compositions of the conductor 61, the glass frit 621, and the high melting point oxide 622 can be measured by component analysis using an electron probe microanalyzer (EPMA) during cross-sectional observation. It is preferable to perform the component analysis at least at three or more locations and calculate the composition of each element (61, 621, 622) from the average value of the measurement results. In this embodiment, when performing the component analysis using an EPMA, an EDS (energy dispersive spectrometer) or a WDS (wavelength dispersive spectrometer) can be used as the X-ray spectrometer.

[0061] The area ratio (A1, A2) of the conductor 61 can be measured by image analysis of a cross-sectional photograph obtained by cross-sectional observation with SEM or STEM. When the cross-section of the baked electrode layer 6a is observed with a backscattered electron image of SEM or a HAADF image of STEM, the conductor 61 having a metallic bond can be recognized as a bright contrast area, and the non-metallic components 62 such as the glass frit 621 (including voids and oxides) can be recognized as a dark contrast area. Therefore, the area ratio of the conductor 61 in the cross-section of the baked electrode layer 6a can be calculated as the ratio of the area of ​​the bright contrast area to the area of ​​the entire measurement field by, for example, binarizing the cross-sectional photograph. It is preferable to measure this area ratio in at least five fields of view and calculate the average value.

[0062] In the above-described cross-sectional observation, the boundary between the first region 6a and the second region 6a2 may or may not be visible. Therefore, when measuring the average area ratio A1 in the first region 6a1, the observation field of view is set within the range of the above-described predetermined distance t1. Similarly, when measuring the average area ratio A2 in the second region 6a2, the observation field of view is set within the range of the above-described predetermined distance t2.

[0063] In the above cross-sectional observation, non-metallic components 62 including glass frit 621, high-melting-point oxide 622, other oxides, voids, etc. are present in the areas other than the conductor 61 (areas with dark contrast). In the composition images of SEM or STEM, it is not easy to distinguish the difference between oxide and glass, or between oxide and voids, by the light and dark of the contrast. Therefore, it is difficult to measure the ratio of glass and oxide in the non-metallic components 62. However, when these ratios are roughly calculated, the non-metallic components 62 in the first region 6a1 mainly include glass frit 621, and the number ratio of the glass frit 621 is greater than the number ratio of the high-melting-point oxide 622, other oxides, voids, etc. In addition, the non-metallic components 62 in the second region 6a2 mainly include high-melting-point oxide 622, and the number ratio of the high-melting-point oxide 622 is greater than the number ratio of the glass frit 621, other oxides, voids, etc. The number ratio can be roughly calculated by analyzing the components of the nonmetallic components 62 contained in each region by point analysis using an EPMA.

[0064] Next, an example of a method for manufacturing the multilayer ceramic capacitor 2 shown in FIG. 1A will be described.

[0065] First, a description will be given of the manufacturing process of the element body 4. In the manufacturing process of the element body 4, a dielectric paste that becomes the ceramic layers 10 after firing and an internal electrode paste that becomes the internal electrode layers 12 after firing are prepared.

[0066] The dielectric paste is manufactured, for example, by the following method. First, the dielectric raw material is mixed uniformly by means of wet mixing or the like, and dried. Then, the mixture is heat-treated under predetermined conditions to obtain calcined powder. Next, a known organic vehicle or a known aqueous vehicle is added to the calcined powder obtained and kneaded to prepare a dielectric paste. The dielectric paste thus obtained is formed into a sheet by a method such as a doctor blade method to obtain a ceramic green sheet. The dielectric paste may contain additives selected from various dispersants, plasticizers, dielectrics, auxiliary component compounds, glass frits, etc., as necessary.

[0067] On the other hand, the internal electrode paste is prepared by kneading a conductive powder made of a conductive metal or its alloy with a known binder and solvent. The internal electrode paste may contain a ceramic powder (e.g., calcium strontium zirconate powder) as a co-material, if necessary. The co-material has the effect of suppressing the sintering of the conductive powder during the firing process.

[0068] Next, the internal electrode paste is applied in a predetermined pattern onto the ceramic green sheets by various printing methods such as screen printing or transfer methods. The green sheets on which the internal electrode patterns are formed are then stacked in multiple layers, and pressed in the stacking direction to obtain a mother laminate. At this time, the ceramic green sheets and the internal electrode patterns are stacked so that the ceramic green sheets are located on the upper and lower surfaces of the mother laminate in the stacking direction.

[0069] The mother laminate obtained by the above process is cut into a predetermined size by dicing or pressing to obtain a plurality of green chips. The green chips may be solidified and dried to remove plasticizers, etc., as necessary, and may be barrel-polished using a horizontal centrifugal barrel machine or the like after solidification and drying. In barrel polishing, the green chips are placed in a barrel container together with media and polishing liquid, and the barrel container is given rotational motion, vibration, etc., to polish away unnecessary parts such as burrs generated during cutting. After barrel polishing, the green chips are washed with a cleaning liquid such as water and dried.

[0070] Next, the green chip obtained above is subjected to a binder removal process and a firing process, and the element body 4 is obtained.

[0071] The conditions for the binder removal treatment are not particularly limited and may be appropriately determined depending on the main component composition of the ceramic layer 10 and the main component composition of the internal electrode layer 12. For example, the temperature increase rate is preferably 5 to 300°C / hour, the holding temperature is preferably 180 to 400°C, and the temperature holding time is preferably 0.5 to 24 hours. The binder removal atmosphere is air or a reducing atmosphere.

[0072] The firing conditions are not particularly limited and may be appropriately determined depending on the main component composition of the ceramic layers 10 and the main component composition of the internal electrode layers 12. For example, the holding temperature during firing is preferably 1200 to 1400°C, more preferably 1220 to 1300°C, the holding time is preferably 0.5 to 8 hours, more preferably 1 to 3 hours, and the heating rate and cooling rate (temperature drop rate) are preferably 50 to 500°C / hour. The firing atmosphere is preferably a reducing atmosphere, and the atmospheric gas may be, for example, N 2 and H 2 In addition, when the internal electrode layer 12 is made of a base metal such as Ni or a Ni alloy, the oxygen partial pressure in the firing atmosphere is set to 1.0×10 -14 ~1.0×10 -10 It is preferable that the pressure is set to MPa.

[0073] After firing, the obtained element body 10 may be subjected to a reoxidation treatment (annealing) as necessary. The annealing conditions are preferably, for example, an oxygen partial pressure during annealing higher than that during firing, and a holding temperature of 1150° C. or lower.

[0074] In the above-mentioned binder removal treatment, firing treatment and annealing treatment, N 2 In order to humidify the gas or mixed gas, for example, a wetter or the like may be used, and in this case, the water temperature is preferably about 5 to 75° C. Furthermore, the binder removal treatment, firing treatment, and annealing treatment may be performed consecutively or independently.

[0075] Next, the baked electrode layer 6a is formed on the outer surface of the element body 4 obtained above. In forming the baked electrode layer 6a, first, a first conductive paste for forming the first region 6a1 and a second conductive paste for forming the second region 6a2 are prepared. The first conductive paste contains a metal powder and a glass frit 621 that will become the conductor 61 after baking. On the other hand, the second conductive paste contains a metal powder and a powder of a high melting point oxide 622 that will become the conductor 61 after baking. In addition to the above, the first conductive paste and the second conductive paste may contain, as appropriate, auxiliary component raw materials such as a binder, a solvent, a dispersant, a plasticizer, and an oxide powder.

[0076] The glass frit 621 to be added to the paste can be produced, for example, by the following procedure. 2 powder, B 2 O 3 Powder, CaCO 3 Powder, SrCO 3 After mixing the starting materials such as ZnO powder and other oxide powders in a predetermined ratio, the mixture is heated and melted in a crucible. The molten mixture is then dropped into water and quenched to obtain glass. The obtained glass is then crushed to a predetermined particle size using a mortar or ball mill to obtain glass frit 621. At this time, the composition of glass frit 621 may be adjusted by adjusting the compounding ratio of the starting materials. On the other hand, the high melting point oxide 622 is made of ZnO powder, SiO 2 The high melting point oxide 622 can be manufactured by mixing starting materials such as powders in a predetermined ratio, calcining the mixture, and pulverizing it to a predetermined particle size. The composition of the high melting point oxide 622 can be adjusted by adjusting the compounding ratio of the starting materials.

[0077] Moreover, the area proportions A1 and A2 of the conductor 61 may be adjusted by the compounding ratio of the metal powder added to each conductive paste.

[0078] The binder, solvent, and dispersant used in each conductive paste are not particularly limited and may be the same as those used in the dielectric paste. For example, the binder may be appropriately selected from various common binders such as acrylic, butyral, and ethyl cellulose, and the solvent may be appropriately selected from various organic solvents and aqueous solvents such as alcohol, methyl ethyl ketone, acetone, toluene, terpineol, and butyl carbitol.

[0079] After preparing the above-mentioned two kinds of conductive paste, the first conductive paste is applied to the outer surface of the element body 4 by a dipping method or a printing method and dried. Then, the element body 4 is held at a temperature of 700°C to 1000°C for 0.1 to 3 hours to bake the first conductive paste. Then, the second conductive paste is applied on the baked first conductive paste by a dipping method or a printing method and dried. Then, the element body 4 is held at a temperature of 700°C to 1000°C for 0.1 to 3 hours to bake the second conductive paste. This makes it possible to form a baked electrode layer 6a having a predetermined first region 6a1 and second region 6a2. In the above-mentioned method, the first conductive paste and the second conductive paste are baked separately, but they may be baked simultaneously.

[0080] After the baked electrode layer 6a is formed, a plating process such as electrolytic plating or electroless plating can be performed to form a plated electrode layer 6b on the baked electrode layer 6a. A resin electrode may be formed on the baked electrode 6a. In this case, a conductive paste for a resin electrode containing a thermosetting resin may be applied to cover the baked electrode 6a by a dipping method or a printing method, and then a hardening process may be performed. A plated electrode layer may be further formed on the resin electrode.

[0081] Through the above steps, a multilayer ceramic capacitor 2 having external electrodes 6 is obtained.

[0082] The obtained multilayer ceramic capacitor 2 can be surface-mounted on a substrate such as a printed wiring board using solder (including molten solder, solder cream, and solder paste) or a conductive adhesive, and used in various electronic devices, etc. Alternatively, the multilayer ceramic capacitor 2 can be mounted on a substrate via a wire-shaped lead terminal or a plate-shaped metal terminal.

[0083] (Summary of the first embodiment) The multilayer ceramic capacitor 2 according to this embodiment has a fired electrode layer 6a including a conductor 61 containing Cu and a non-metallic component 62 dispersed in the conductor 61. The fired electrode layer 6a has a first region 6a1 in contact with the end face 4a of the element body 4 and a second region 6a2 in contact with the plated electrode layer 6b, with the first region 6a1 including a glass frit 621 including a predetermined element and the second region 6a2 including a high-melting point oxide 622 having a melting point higher than that of Cu.

[0084] The inventors have found that the multilayer ceramic capacitor 2 having the above-mentioned configuration improves the plating properties of the fired electrode layers 6a and improves the bonding reliability of the external electrodes 6 to the element body. That is, in the multilayer ceramic capacitor 2 of this embodiment, plating defects are suppressed and the solder wettability of the external electrodes 6 is improved. Furthermore, the multilayer ceramic capacitor 2 can prevent the external electrodes 6 from peeling off from the end faces 4a of the element body 4 even when subjected to thermal shock.

[0085] In particular, by ensuring that the glass frit 621 or the high melting point oxide 622 has a predetermined composition ratio, it is possible to more suitably achieve both the plating properties and the bonding reliability of the fired electrode layer 6a.

[0086] The reason why the above-mentioned effect is obtained is not necessarily clear, but the following reasons are considered to be the cause.

[0087] First, in this embodiment, the second region 6a2 containing the high melting point oxide 622 exists on the outer surface 6ab of the baked electrode layer 6a in contact with the plated electrode layer 6b. It is considered that the presence of the high melting point oxide 622 in the vicinity of the outer surface 6ab in this way can suppress the deposition of the glass frit 621 on the outer surface 6ab of the baked electrode layer 6a. As a result, it is possible to suppress the occurrence of plating defects when forming the plated electrode layer 6b on the baked electrode layer 6a.

[0088] In this embodiment, the first region 6a1 bonded to the end face 4a of the element body 4 contains a glass frit 621 containing a predetermined element. The glass frit 621 softens during firing and enters into the conductor 61 and between the conductor 61 and the end face 4a, which is thought to improve the bonding strength of the fired electrode layer 6a to the element body 4. As a result, in the multilayer ceramic capacitor 2, peeling of the external electrode 6 from the end face 4a of the element body 4 can be suppressed even if the multilayer ceramic capacitor 2 is subjected to thermal shock.

[0089] Second embodiment Hereinafter, a second embodiment of the present invention will be described with reference to Figures 1B and 2B. Note that, for configurations in the second embodiment common to the first embodiment, descriptions will be omitted and the same reference numerals will be used.

[0090] In the second embodiment, a boundary layer 14 is interposed between the external electrode 6 and the ceramic layer 10 of the element body 4 (see FIG. 2B). This boundary layer 14 exists at the end of the ceramic layer 10 in the X-axis direction, and constitutes part of the outermost surface of the end face 4a of the element body 4. Although not shown in FIG. 1B, when the external electrode 6 is formed spanning from the end face 4a to part of the side face 4b, it is preferable that the boundary layer 14 exists not only on the end face 4a but also on the outermost surface of the side face 4b.

[0091] In the cross section shown in FIG. 2B, the internal electrode layer 12 penetrates the boundary layer 14 and is exposed at the end face 4a, and the exposed end of the internal electrode layer 12 is electrically connected to the baked electrode layer 6a (particularly the conductor 61) of the external electrode 6. However, when observing the XZ cross section, there may be a portion at the end face 4a where the boundary layer 14 covers the end (end in the X-axis direction) of some of the internal electrode layers 12. Each internal electrode layer 12 exists along the Y-axis direction, and as long as the end of each internal electrode layer 12 penetrates the boundary layer 14 at least partially and is in direct contact with the baked electrode layer 6a, even if the end is partially covered by the boundary layer 14, the electrical connection between each internal electrode layer 12 and the external electrode 6 can be ensured. In addition, a part of the external electrode 6 may penetrate into the boundary layer 14, and the joint boundary 46 between the external electrode 6 and the end face 4a (boundary layer 14 or internal electrode layer 12) of the element body 4 may be unclear.

[0092] The average length Lr (average thickness) of the boundary layer 14 in the X-axis direction is preferably 0.5 μm to 10 μm, and more preferably 1 μm to 5 μm.

[0093] The boundary layer 14 is preferably composed mainly of an oxide containing a predetermined element. The main component of the boundary layer 14 refers to a component that is contained in an amount of 50 mol % or more with respect to the entire boundary layer 14. The predetermined element is Zn, Si, and an A-site element (preferably Ca and / or Sr) of the perovskite compound contained in the ceramic layer 10.

[0094] Moreover, the main component oxide of the boundary layer 14 is preferably a non-vitrified crystalline oxide, and specifically, preferably satisfies the following composition: If the sum of the content of Zn, the content of Si, and the content of the A-site elements is taken as 1 part by mol, the content of the A-site elements is preferably 0.3 parts by mol to 0.45 parts by mol, the content of Zn is preferably 0.15 parts by mol to 0.45 parts by mol, and the remainder is Si (preferably 0.2 parts by mol to 0.45 parts by mol).

[0095] Among the oxides that satisfy the above composition ratio, (Ca, Sr) 2 Zn(Si2 O 7 ) is preferably contained in the boundary layer 14. The ratio of Ca to Sr in the above composition formula is not particularly limited.

[0096] In addition to the above-mentioned main component oxides, the boundary layer 14 contains other compounds such as ZrO 2 or / and a main component compound (perovskite type compound) of the ceramic layer 10. The above compound can be included in the boundary layer 14 by intentionally adding it to the raw material paste for forming the boundary layer 14. However, it is also conceivable that the above compound diffuses from the ceramic layer 10 and enters the boundary layer 14, and the content of the above compound in the boundary layer 14 is not particularly limited.

[0097] The boundary layer 14 may further contain trace compounds including Al, Ti, Ca, B, etc. The boundary layer 14 may also contain conductive metal components such as Cu and Ni. The contents of the trace compounds and metal components are not particularly limited.

[0098] The boundary layer 14 having the above characteristics functions to improve the bonding strength between the ceramic layer 10 of the element body 4 and the fired electrode layer 6a. In particular, a part of the glass frit 621 contained in the fired electrode layer 6a is in direct contact with a part of the boundary layer 14, thereby further improving the bonding strength of the fired electrode layer 6a to the end face 4a. Both the glass frit 621 and the boundary layer 14 contain Zn, Si, and A-site elements (Ca, Sr), and it is believed that the mutual diffusion of these common elements between the glass frit 621 and the boundary layer 14 improves the bonding strength of the fired electrode layer 6a.

[0099] In addition, the particles of the glass frit 621 directly in contact with the boundary layer 14 preferably have a shape that provides an anchor effect. The "particle shape that provides an anchor effect" means that the particles do not spread thinly along the outer surface (YZ plane) of the boundary layer 14, but rather spread three-dimensionally from the outer surface of the boundary layer 14 toward the inside of the baked electrode layer 6a (i.e., toward the outside in the X-axis direction) as shown in FIG. 2B. That is, the particles of the glass frit 621 located at the bond boundary 46 penetrate from the bond boundary 46 toward the gaps in the conductor 61, providing an anchor effect as if the barbs of the hooks are biting in, and the bond strength of the external electrode 6 to the element body 4 is further improved. The above-mentioned anchor effect can be achieved by controlling the particle shape of the glass frit added to the raw material paste of the baked electrode layer 6a.

[0100] The boundary layer 14 can be analyzed by cross-sectional observation using a SEM, STEM, or the like, in the same manner as the baked electrode layer 6a. For example, the average length Lr of the boundary layer 14 can be measured by image analysis of a cross-sectional photograph. The composition of the boundary layer 14 can be measured by component analysis using an EPMA.

[0101] The boundary layer 14 can be formed by subjecting the first conductive paste to high temperature baking treatment or by using a boundary layer paste, and it is preferable to adopt a method using a boundary layer paste. Note that the boundary layer 14 may be formed by ceramic coating using various deposition methods without using a paste.

[0102] When a high-temperature baking process is employed, the holding temperature is preferably set to more than 800°C (more preferably 850°C or higher) and 1100°C or lower, and the holding time is preferably set to 0.5 to 3 hours. By baking the first conductive paste at a higher temperature or for a longer time than in a normal baking process, the boundary layer 14 is formed.

[0103] When using a boundary layer paste, the boundary layer 14 can be formed by applying and baking the boundary layer paste to the outer surface of the green chip before firing or the outer surface of the element body 4 after firing.

[0104] In this case, the paste for the boundary layer contains a raw material powder for the boundary layer, a binder, and a solvent, and may further contain a dispersant, a plasticizer, etc., as necessary. The raw material powder for the boundary layer is ZnO powder and SiO 2 Powder and B 2 O 3 Powder, CaCO 3 Powder, SrCO 3 The starting materials for the boundary layer are mixed in a predetermined ratio, calcined, and pulverized. In addition to the above, the raw material powder for the boundary layer may also contain powder of a dielectric compound, which is the main component of the ceramic layer 10, ZrO 2 Powder, Al 2 O 3 Powder of a trace compound such as Cu powder, Ni powder, or powder of an alloy containing Cu, Ni, or the like may also be added.

[0105] The boundary layer paste can be applied to the green chip or element body 4 by a dipping method, various printing methods such as screen printing, application methods using a dispenser, spraying methods using a spray, etc. The boundary layer paste is applied to at least the end face 4a, and may also be applied to a part of the side face 4b. In this case, the average length Lr (average thickness) of the boundary layer 14 can be adjusted by controlling the amount of the boundary layer paste applied.

[0106] When the boundary layer paste is applied to the element body 4, the boundary layer paste is dried after application and baked at a temperature of 700°C to 1000°C for 0.1 to 3 hours to form the boundary layer 14. In this case, the baking of the boundary layer paste may be performed simultaneously with the baking of the first conductive paste. The average length Lr of the boundary layer 14 is also affected by the baking conditions. If the temperature during the baking process is set low or the holding time is shortened, the average length Lr tends to become smaller (the average thickness becomes thinner). In addition to the above, the average length Lr can also be affected by the amount of the boundary layer paste applied. When the boundary layer paste is applied to the green chip, the boundary layer paste is baked when the green chip is fired.

[0107] When the boundary layer is formed using a paste, it is preferable to perform sandblasting or wet barrel polishing on the end face 4a of the element body 4 before applying the paste and / or after baking the paste. In sandblasting or wet barrel polishing, the ceramic component (ceramic layer 10 or boundary layer 14) is selectively polished rather than the end of the internal electrode layer 12, and the end of the internal electrode layer 12 is easily exposed on the top surface of the end face 4a. In other words, by performing sandblasting or wet barrel polishing, the electrical connection of the internal electrode layer 12 to the external electrode 6 is improved. Even if sandblasting or wet barrel polishing is not performed, the electrical connection between the external electrode 6 and the internal electrode layer 12 can be secured to a certain degree. This is because, after the conductive material of the internal electrode layer 12 reacts with the conductive material of the external electrode 6, the glass frit 621, the oxide constituting the boundary layer 14, and the main component (ABO) of the ceramic layer 10 are mixed together. 3 ) reacts with each other, so that oxides due to the boundary layer paste are unlikely to be formed at the ends of the internal electrode layers 12 in the X-axis direction.

[0108] (Summary of the second embodiment) In the multilayer ceramic capacitor 2 of the second embodiment, a boundary layer 4 containing a predetermined element is present between the fired electrode layer 6a and the ceramic layer 10. The presence of the boundary layer 14 further improves the bonding reliability of the external electrode 6. The reason why this effect is obtained is not necessarily clear, but it is believed that the interdiffusion phenomenon contributes to the improvement of the bonding reliability.

[0109] Specifically, in the multilayer ceramic capacitor 2, the boundary layer 14 is present at the joint with the external electrode 6, so that Ca, Sr, Zn, Si, etc. become common elements between the element body 4 and the external electrode 6. It is believed that the presence of multiple common elements in this way causes the multiple common elements to interdiffuse between the fired electrode layer 6a and the boundary layer 14. As a result, the bonding strength of the external electrode 6 to the element body 4 is improved.

[0110] In particular, it is considered that the boundary layer 14, which satisfies a predetermined composition ratio, acts to relieve thermal stress occurring between the element body 4 and the external electrode 6. There is a difference in linear expansion coefficient between the fired electrode layer 6a containing the amorphous glass frit 621 and the crystalline ceramic layer 10. On the other hand, when the boundary layer 14 has a predetermined composition, it is considered that the boundary layer 14 has a linear expansion coefficient close to that of the ceramic layer 10, and the difference in linear expansion coefficient between the external electrode 6 and the element body 4 is smaller than when the boundary layer 14 does not exist. As a result, it is considered that thermal stress is less likely to occur at the joint boundary 46 between the element body 4 and the fired electrode 6a, and resistance to thermal shock is further improved.

[0111] The multilayer ceramic capacitor 2 of the second embodiment is similar to the first embodiment except for having the boundary layer 14, and provides the same effects as the first embodiment.

[0112] Although an embodiment of the present invention has been described above, the present invention is not limited to the above-described embodiment, and various modifications can be made without departing from the spirit of the present invention.

[0113] For example, in this embodiment, the multilayer ceramic capacitor 2 is exemplified as the ceramic electronic component, but the ceramic electronic component of the present invention may be, for example, a bandpass filter, a multilayer three-terminal filter, a piezoelectric element, a thermistor, a varistor, or the like.

[0114] In this embodiment, the ceramic layers 10 and the internal electrode layers 12 are laminated in the Z-axis direction, but the lamination direction may be the X-axis direction or the Y-axis direction. In this case, the external electrode 6 may be formed in accordance with the exposed surface of the internal electrode layer 12. The element body 4 does not necessarily have to be a laminate, and may be a single layer. Furthermore, the internal electrode layer 12 may be drawn to the outer surface of the element body 4 via a through-hole electrode, in which case the through-hole electrode and the external electrode 6 are electrically connected. EXAMPLES

[0115] The present invention will now be described in more detail with reference to examples, but the present invention is not limited to these examples.

[0116] (Experiment 1) In experiment 1, multilayer ceramic capacitors 2 according to Examples 1 and 2 were fabricated according to the following procedure. First, a dielectric paste and an internal electrode paste were prepared, and green chips were fabricated by a sheet method using these pastes. In this case, calcium strontium zirconate (composition formula: (Ca 0.7 Sr 0.3 )(Zr 0.96 Ti 0.04 )O 3 In each of the examples, SiO was used as a secondary component of the ceramic layer 10. 2 , MnO, Al 2 O 3 The internal electrode layer 12 mainly contains Ni.

[0117] Next, the green chip obtained above was subjected to a binder removal process under the conditions described in the embodiment, and then a firing process was performed to obtain the element body 4. The firing process conditions were as follows: holding temperature: 1300° C., holding time: 2 hours, atmospheric gas: humidified N 2 +H 2 The gas mixture was used. The element body 4 was then subjected to an annealing treatment under the conditions described in the embodiment.

[0118] Next, a first conductive paste and a second conductive paste for the fired electrode layer were prepared. The first conductive paste of Example 1 contained Cu powder constituting the conductor 61 and B-Zn-Si based glass frit 621 as the non-metallic component 62. On the other hand, the first conductive paste of Example 2 contained Cu powder constituting the conductor 61 and B-Zn-Si-Ca-Sr based glass frit 621 as the non-metallic component 62. In both Examples 1 and 2, the second conductive paste contained Cu powder and Zn 2 SiO 4 Powder (high melting point oxide 622) was added.

[0119] Next, the first conductive paste was applied to the outer surface (end surface 4a and part of side surface 4b) of element body 4 by dipping and dried. After that, element body 4 was held at 800°C for 0.5 hours to bake the first conductive paste and form part of baked electrode layer 6a. Furthermore, after the first conductive paste was baked, second conductive paste was applied by dipping and dried. After that, element body 4 was held at 800°C for 0.5 hours to bake the second conductive paste and form baked electrode layer 6a having first region 6a1 and second region 6a2.

[0120] Furthermore, a Ni-plated electrode layer and a Sn-plated electrode layer were formed on the baked electrode layer 6a. In this manner, a capacitor sample (multilayer ceramic capacitor 2) having an external electrode 6 formed thereon was obtained. More than 300 capacitor samples were manufactured for each of Examples 1 and 2.

[0121] In each of Examples 1 and 2 of Experiment 1, the dimensions of the element body 4 of the capacitor sample were L0×W0×T0=2.0 mm×1.25 mm×1.25 mm. The number of laminated ceramic layers 10 sandwiched between the internal electrode layers 12 was 80.

[0122] In addition, samples for destructive testing were extracted from the capacitor samples according to each of Examples 1 and 2, and cross-sectional observations were performed using the samples by SEM. Specifically, the extracted samples were cut along the XZ plane, and the cross-sections were mirror-polished. After that, the average thickness Td of the ceramic layers 10, the average thickness Te of the internal electrode layers 12, the average thickness Ts of the fired electrode layers 6a, and the average thickness Tt of the external electrodes 6 on the end faces were measured by SEM. The measurement results for Examples 1 and 2 were as follows.

[0123] Average thickness Td of ceramic layer 10: 10 μm Average thickness Te of the internal electrode layer 12: 1.5 μm Average thickness Ts of baked electrode layer 6a: 36 μm Average thickness of external electrode 6 Tt: 46 μm

[0124] In addition, in the above cross-sectional observation, component analysis was performed by EPMA on the conductor 61 and nonmetallic components 62 (glass frit 621, high melting point oxide 622) contained in the fired electrode layer 6a. As a result, it was confirmed that the composition of the raw material powder added to the raw material paste (first conductive paste, second conductive paste) and the measurement results were generally consistent in all examples. In addition, in the cross-sectional observation, it was confirmed that the first region 6a1 contained glass frit 621 and the second region 6a2 contained high melting point oxide 622 in all examples.

[0125] In experiment 1, a solder wettability test was performed to evaluate the plating properties (presence or absence of plating defects) of the prepared capacitor samples. In addition, a thermal shock test (cooling and heating cycle test) was performed to evaluate the bonding reliability of the external electrodes 6 of the prepared capacitor samples. Details are described below.

[0126] Solder wettability test In the solder wettability test, first, as a pretreatment for the test, the capacitor sample was kept in a thermostatic chamber (PCT chamber) controlled at a temperature of 105°C and a relative humidity of 100%RH for 4 hours. Then, the capacitor sample was immersed in a solder bath at 245°C for 3 seconds. At this time, Sn-Ag-Cu solder was used, and 0.1 mm of the end face side of the capacitor sample was immersed in the solder bath. Then, after the capacitor sample was pulled out of the solder bath, the end face 4a of the capacitor sample was observed, and the area of ​​the end face 4a that the solder had spread by wetting was measured.

[0127] Here, the relationship between the solder wetting and spreading area and plating properties will be explained. Plating defects include adhesion abnormalities such as peeling or swelling of the plating electrode, non-deposition abnormalities such as stains, spots, pits, and pinholes, and abnormalities due to foreign matter adhesion. When such plating defects exist, the wettability of the plating electrode to the solder tends to decrease. Therefore, as described above, by measuring the wetting and spreading area of ​​the solder on the end face, it is possible to indirectly evaluate the presence or absence of plating defects and the ease of plating formation.

[0128] In the solder wettability test of this embodiment, the case where the area of ​​the end face 4a where the solder spread was 95% or more was judged as pass, and the case where it was less than 95% was judged as fail. The test was performed on 10 capacitor samples for each embodiment, and the ratio of samples that failed (NG ratio) was calculated. The evaluation results are shown in Table 1.

[0129] Air tank thermal shock test In the air-bath thermal shock test, the capacitor sample was held in an air bath at -55°C for 30 minutes, then held in an air bath at 150°C for 30 minutes, and this cycle was repeated 1000 times. In this test, the pass / fail was judged based on the capacitance decay rate, and the capacitance C before the test was α After testing, the capacitance C β The ratio of (C β / C α) was rated as passing when it was 0.9 (90%) or more, and as failing when it was less than 0.9. In experiment 1, the above test was carried out on 80 samples for each example, and the ratio of failing samples (NG ratio) was calculated. The evaluation results are shown in Table 1.

[0130] In Experiment 1, in addition to the above-mentioned Examples 1 and 2, capacitor samples according to Comparative Examples 1 and 2 were manufactured.

[0131] Comparative Example 1 In Comparative Example 1, a capacitor sample was manufactured in which a baked electrode layer was formed only with the first conductive paste. Cu powder and B-Zn-Si-Ca-Sr-based glass frit were added to the first conductive paste of Comparative Example 1, and no high melting point oxide was added. Then, only the first conductive paste was applied to the outer surface of the element body 4 and baked to form a baked electrode layer. At this time, the amount of paste applied was controlled so that the average thickness of the baked electrode layer made only of the first conductive paste was approximately the same as the average thickness Ts of the baked electrode layer 6a in Examples 1 and 2. In Comparative Example 1, the manufacturing conditions were the same as those of Examples 1 and 2 described above, except that the second conductive paste was not used, and Comparative Example 1 was evaluated in the same manner as Examples 1 and 2. The evaluation results are shown in Table 1.

[0132] Comparative Example 2 In Comparative Example 2, a capacitor sample was manufactured in which a baked electrode layer was formed using only the second conductive paste. The second conductive paste in Comparative Example 2 contained Cu powder and Zn 2 SiO 4 Powder was added, and glass frit was not added. Then, only the second conductive paste was applied to the outer surface of the element body 4 and baked to form a baked electrode layer. At this time, the amount of paste applied was controlled so that the average thickness of the baked electrode layer made only of the second conductive paste was approximately the same as the average thickness Ts of the baked electrode layer 6a in Examples 1 and 2. In Comparative Example 2, the manufacturing conditions were the same as those of Examples 1 and 2 described above, except that the first conductive paste was not used, and Comparative Example 2 was evaluated in the same manner as Examples 1 and 2. The evaluation results are shown in Table 1.

[0133] [Table 1]

[0134] As shown in Table 1, in Comparative Example 1, in which a baked electrode layer not containing a specified high melting point oxide was formed, the NG ratio in the solder wettability test was 2 / 10. In addition, in Comparative Example 2, in which a baked electrode layer not containing a specified glass frit was formed, the NG ratio in the air tank thermal shock test was 2 / 80. From these results, it can be seen that it is difficult to satisfy both plating properties and bonding reliability with conventional technology.

[0135] On the other hand, in both Examples 1 and 2 according to the present invention, the NG rate in the solder wettability test and the NG rate in the air-tank thermal shock test were 0%, and the plating properties and bonding reliability were improved compared to Comparative Examples 1 and 2. From these results, it was confirmed that by containing a predetermined glass frit 621 in the vicinity of the bonding boundary 46 in the baked electrode layer 6a and a predetermined high-melting point oxide in the vicinity of the interface with the plated electrode layer 6b (in the vicinity of the outer surface 6ab), it is possible to improve both the plating properties and the bonding reliability.

[0136] (Experiment 2) In experiment 2, the composition of the glass frit 621 contained in the first region 6a1 was changed to produce capacitor samples according to examples 3 to 5. 2 O 3 powder, ZnO powder, and SiO 2 The starting materials were mixed with and calcined, and then pulverized to obtain glass frit 621. At this time, the compounding ratio of the starting materials was adjusted to control the contents of B, Zn, and Si contained in glass frit 621. Then, a first conductive paste was prepared using glass frit 621 obtained above, and a capacitor sample was manufactured in the same manner as in Example 1 of Experiment 1. That is, in Examples 3 to 5, Zn was added to second region 6a2, and 2 SiO 4 Powder (high melting point oxide 622) was included.

[0137] The composition of the glass frit 621 contained in the obtained capacitor sample was measured by component analysis using SEM-EPMA. The measurement results for each of Examples 3 to 5 are shown in Table 2.

[0138] In addition, in Experiment 2, a solder wettability test and an air-bath thermal shock test were performed in the same manner as in Experiment 1. The evaluation results are shown in Table 2.

[0139] [Table 2]

[0140] As shown in Table 2, the NG rates in the solder wettability test and the air-bath thermal shock test were both 0% in Examples 3 to 5. From this result, it was confirmed that when the composition of the glass frit 621 was within the range of Examples 3 to 5, both plating properties and bonding reliability were satisfied.

[0141] (Experiment 3) In experiment 3, the composition of the high melting point oxide 622 contained in the second region 6a2 was changed to manufacture capacitor samples according to examples 6 and 7. Specifically, in experiment 3, ZnO powder and SiO 2 The powder was used as starting materials, which were mixed, calcined, and then pulverized to obtain a powder of high melting point oxide 622. At this time, the content of Zn and Si contained in high melting point oxide 622 was controlled by adjusting the compounding ratio of the starting materials. Then, a second conductive paste was prepared using the powder obtained above, and a capacitor sample was manufactured in the same manner as in Example 1 of Experiment 1. That is, in Examples 6 and 7, B-Zn-Si-based glass frit 621 was contained in first region 6a1.

[0142] The composition of the high melting point oxide 622 contained in the obtained capacitor sample was measured by component analysis using SEM-EPMA. The measurement results for each of Examples 6 and 7 are shown in Table 3.

[0143] In addition, in Experiment 3, a solder wettability test and an air-bath thermal shock test were performed in the same manner as in Experiment 1. The evaluation results are shown in Table 3.

[0144] [Table 3]

[0145] As shown in Table 3, the NG rates of the solder wettability test and the air-bath thermal shock test were both 0% in Examples 6 and 7. From these results, it was confirmed that when the composition of the high melting point oxide 622 was within the range of Examples 6 and 7, both plating properties and bonding reliability were satisfied.

[0146] (Experiment 4) In experiment 4, a capacitor sample of Example 11 in which a boundary layer 14 was not formed, and capacitor samples of Examples 12 to 14 in which a boundary layer 14 was formed were manufactured, and the effect of the presence or absence of boundary layer 14 on the bonding reliability was evaluated.

[0147] Example 11 In Example 11, a capacitor sample was manufactured under the same conditions as in Example 1 of Experiment 1. That is, in Example 11, the first region 6a1 of the baked electrode layer 6a contained B-Zn-Si based glass frit 621, and the second region 6a2 of the baked electrode layer 6a contained Zn 2 SiO 4 The high melting point oxide 622 was comprised of:

[0148] Example 12 In Example 12, the first conductive paste was subjected to a high-temperature baking process to form a boundary layer 14 between the baked electrode layer 6a and the ceramic layer 10. Specifically, the first conductive paste was baked by holding it at a temperature of 900° C. for 0.5 hours. The other experimental conditions were the same as those of Example 11, and a capacitor sample according to Example 12 was obtained.

[0149] When the cross section of the capacitor sample obtained above was observed by SEM in the same manner as in Experiment 1, it was confirmed that in Example 12, a boundary layer 14 having an average length Lr of 1.5 μm was formed, and the boundary layer 14 contained (Ca,Sr)ZnSi 2 O6 It was confirmed that it contains.

[0150] Example 13 In Example 13, the boundary layer paste was applied to the green chip before firing, and the boundary layer paste was baked at the same time as the green chip was fired to form the boundary layer 14 between the fired electrode layer 6a and the ceramic layer 10. At this time, the boundary layer paste contained (Ca, Sr) 2 Zn(Si 2 O 7 ) powder, which is CaCO 3 Powder and SrCO 3 powder, ZnO powder, and SiO 2 The powder was used as a starting material and calcined to obtain a capacitor sample according to Example 13. In addition, in Example 13, the end face 4a of the element body 4 after sintering was subjected to wet barrel polishing. The other experimental conditions were the same as those of Example 11, and a capacitor sample according to Example 13 was obtained.

[0151] When the cross section of the capacitor sample of Example 13 was observed by SEM in the same manner as in Experiment 1, it was confirmed that a boundary layer 14 having an average length Lr of 1.8 μm was formed in Example 13, and that the boundary layer 14 contained an oxide having the composition shown in Table 4.

[0152] Example 14 In Example 14, the boundary layer paste was applied to the outer surface of the fired element body 4 and baked at 900° C. for 0.5 hours to form the boundary layer 14 between the baked electrode layer 6a and the ceramic layer 10. At this time, the boundary layer paste contained (Ca, Sr) 2 Zn(Si 2 O 7 ) powder, which is CaCO 3 Powder and SrCO 3 powder, ZnO powder, and SiO 2The powder was used as a starting material and calcined to obtain a capacitor sample according to Example 14. In Example 14, the end surface 4a of the element body 4 was subjected to wet barrel polishing before the boundary layer paste was applied. The other experimental conditions were the same as those of Example 11, and a capacitor sample according to Example 14 was obtained.

[0153] When the cross section of the capacitor sample of Example 14 was observed by SEM in the same manner as in Experiment 1, it was confirmed that a boundary layer 14 having an average length Lr of 1.9 μm was formed in Example 14, and that the boundary layer 14 contained an oxide having the composition shown in Table 4.

[0154] In Experiment 4, in order to evaluate the bonding reliability of each Example, an air-bath thermal shock test was carried out in the same manner as in Experiment 1. Furthermore, in Experiment 4, a liquid-bath thermal shock test was also carried out under the conditions shown below.

[0155] Liquid bath thermal shock test In the liquid bath thermal shock test, the thermal cycle is performed in a liquid bath instead of an air bath. When using a liquid bath, the capacitor sample is subjected to a steeper temperature change than when using an air bath, so the bonding reliability of the capacitor sample can be evaluated under more severe conditions than in the air bath test. Specifically, in this embodiment, the capacitor sample was held in a liquid bath at -55°C for 30 minutes per cycle, and then held in a liquid bath at 150°C for 30 minutes, and this was repeated 1000 cycles. The pass / fail of the liquid bath thermal shock test was determined based on the capacitance decay rate, as in the air bath thermal shock test. In experiment 4, the above test was performed on 80 samples for each embodiment, and the ratio of samples that failed (NG ratio) was calculated. Table 4 shows the evaluation results of each embodiment in experiment 4.

[0156] [Table 4]

[0157] As shown in Table 4, it was confirmed that the bonding reliability of the fired electrode layer 6a was further improved by forming the boundary layer 14. Moreover, in Examples 13 and 14, the NG rate in the liquid bath thermal shock test was 0%, and it was found that the bonding reliability was further improved by forming the boundary layer 14 using the boundary layer paste.

[0158] (Experiment 5) In experiment 5, the composition of the boundary layer 14 was changed to produce capacitor samples according to examples 15 to 17. The composition of the boundary layer 14 was changed by adding (Ca,Sr)Zn(Si 2 O 7 In the production of the powder, the mixing ratio of the starting materials was adjusted. The other experimental conditions in Experiment 5 were the same as those in Example 14 of Experiment 4.

[0159] Cross-sectional observation by SEM was performed on each of the Examples of Experiment 5, and it was confirmed that a boundary layer 14 having an average length Lr of 2 μm was formed in each of Examples 15 to 17. In addition, a component analysis of the boundary layer 14 was performed by EPMA, and the contents of each element contained in the boundary layer 14 were as shown in Table 5.

[0160] In Experiment 5, the solder wettability test and the liquid bath thermal shock test were carried out under the conditions described above. The evaluation results of each example of Experiment 5 are shown in Table 5.

[0161] [Table 5]

[0162] As shown in Table 5, the NG rates in the solder wettability test and the liquid bath thermal shock test were both 0% in Examples 15 to 17. From these results, it was confirmed that when the content ratio of each element contained in the boundary layer 14 was within the range of Examples 15 to 17, the bonding strength of the baked electrode layer 6a was further improved, and both plating properties and bonding reliability were satisfied.

[0163] (Experiment 6) In experiment 6, the average area ratios A1 and A2 of the conductor 61 in each of the regions 6a1 and 6a2 of the fired electrode layer 6a were changed to produce capacitor samples according to Examples 21 to 24. The average area ratios A1 and A2 of the conductor 61 were controlled by adjusting the compounding ratio of the Cu powder added to the first conductive paste and the second conductive paste. The results of measuring the average area ratios A1 and A2 in each Example by cross-sectional observation with an SEM are shown in Table 6. The area ratios A1 and A2 in each Example were calculated by extracting three samples for destructive testing from the multiple capacitor samples produced and observing the cross-sections of the extracted samples in at least five fields of view.

[0164] The other experimental conditions in Experiment 6 were the same as those in Example 1 in Experiment 1, and capacitor samples according to Examples 21 to 24 were obtained. Also in Experiment 6, a solder wettability test and an air-tank thermal shock test were performed. The evaluation results of Experiment 6 are shown in Table 6.

[0165] [Table 6]

[0166] As shown in Table 6, it was confirmed that when the average area ratios A1 and A2 of the conductor 61 in each region are within a predetermined range, the plating properties and bonding reliability of the fired electrode layer 6a are further improved. [Explanation of symbols]

[0167] 2. Multilayer ceramic capacitors 4 … Element body 4a … End face 4b…side 10 … ceramic layer 12 … Internal electrode layer 14 … boundary layer 6 … External electrode 6a … Baked electrode 6a1 … 1st area 6a2 … 2nd area 61 ... Conductor 62 … Non-metallic components 621 ... Glass frit 622...High melting point oxides 6ab … Outer surface (boundary between baked electrode layer and plated electrode layer) 6b … Plating electrode layer 6b1 ... Ni plating layer 6b2 ... Sn plating layer 46 … Junction boundary

Claims

1. A ceramic electronic component having an element body including a ceramic layer and an internal electrode layer, and an external electrode formed on an end surface of the element body and electrically connected to at least one end of the internal electrode layer, The ceramic layer is made of ABO 3 The perovskite-type compound represented by the formula The external electrodes have baked electrode layers, the fired electrode layer has a first region that is in contact with the end face of the element body and is located near a joint boundary with the element body, and a second region that is located outside the first region and constitutes an outer surface of the fired electrode layer, the first region includes a glass frit including at least B, Zn, and Si; The second region includes an oxide having a melting point higher than that of Cu, The oxide contained in the second region contains Zn and Si as main components, The ceramic electronic component has a molar ratio (Zn / Si) of the Zn content to the Si content in the oxide of 1.5 to 2.

4.

2. In the glass frit included in the first region, When the sum of the B content, the Zn content, and the Si content is 1 part by mol, The Zn content is 0.20 to 0.35 parts by mole, The content of Si is 0.10 to 0.30 parts by mole, 2. The ceramic electronic component according to claim 1, wherein the remainder is B.

3. The oxide contained in the second region is Zn 2 SiO 4 3. The ceramic electronic component according to claim 1 or 2,

4. a boundary layer is present at an end of the ceramic layer that is in contact with the external electrode at the end surface of the element body, 4. The ceramic electronic component according to claim 1, wherein the boundary layer contains Zn, Si, and an A-site element of the perovskite compound.

5. In the boundary layer, When the sum of the Zn content, the Si content, and the A-site element content is taken as 1 molar part, A site element content is 0.3 to 0.45 molar parts; The Zn content is 0.15 to 0.45 parts by mole, 5. The ceramic electronic component according to claim 4, wherein the remainder is Si.

6. The main components of the boundary layer are (Ca, Sr) 2 Zn(Si 2 O 7 6. The ceramic electronic component according to claim 4 or 5, wherein

7. In a cross section of the baked electrode layer, 7. The ceramic electronic component according to claim 1, wherein an area ratio of the conductor to the first region is 30% to 60%.

8. In a cross section of the baked electrode layer, 8. The ceramic electronic component according to claim 1, wherein an area ratio of the conductor to the second region is 70% to 90%.

9. A ceramic electronic component having an element body including a ceramic layer and an internal electrode layer, and an external electrode formed on an end surface of the element body and electrically connected to at least one end of the internal electrode layer, The ceramic layer is made of ABO 3 The perovskite-type compound represented by the formula The external electrodes have baked electrode layers, the fired electrode layer has a first region that is in contact with the end face of the element body and is located near a joint boundary with the element body, and a second region that is located outside the first region and constitutes an outer surface of the fired electrode layer, the first region includes a glass frit including at least B, Zn, and Si; The second region includes an oxide having a melting point higher than that of Cu, The oxide contained in the second region is Zn 2 SiO 4 Ceramic electronic components.

10. A ceramic electronic component having an element body including a ceramic layer and an internal electrode layer, and an external electrode formed on an end surface of the element body and electrically connected to at least one end of the internal electrode layer, The ceramic layer is made of ABO 3 The perovskite-type compound represented by the formula The external electrodes have baked electrode layers, the fired electrode layer has a first region that is in contact with the end face of the element body and is located near a joint boundary with the element body, and a second region that is located outside the first region and constitutes an outer surface of the fired electrode layer, the first region includes a glass frit including at least B, Zn, and Si; The second region includes an oxide having a melting point higher than that of Cu, a boundary layer is present at an end of the ceramic layer that is in contact with the external electrode at the end surface of the element body, the boundary layer contains Zn, Si, and an A-site element of the perovskite compound; A ceramic electronic component, wherein the main component of the boundary layer is (Ca, Sr) 2 Zn(Si 2 O 7 ).

Citation Information

Patent Citations

  • Ceramic capacitor

    JP1992171912A

  • Multilayer ceramic capacitor

    JP2012059742A

  • Multilayer ceramic electronic component

    JP2012244150A

  • Multilayer ceramic electronic component and mounting board thereof

    JP2015216339A

  • Ceramic electronic component and manufacturing method of ceramic electronic component

    JP2019024065A